Training in psychosomatic medicine and psychotherapy for medical doctors in China: A field report - Wei, Jing; Fritzsche, Kurt; Shi, Lili; Cao, Jinya; Bassler, Markus; Müller, Anne-Maria; Zhang, Ying; Lüdemann, Hannah-Theresa; Leonhart, Rainer (Frontiers in Medicine, 2023)
Abstract Background: The high prevalence rates of mental disorders in China contrast a comparatively low care capacity from qualified trained medical doctors in the mental health field. The main objective of our cooperation project was to develop and implement advanced postgraduate training for medical doctors for their acquisition of knowledge, skills, and attitudes in the field of psychosomatic medicine and psychotherapy in China. Methods: Monitoring and evaluation as part of the advanced training in Beijing were conducted following the Kirkpatrick training approach using four levels of evaluation: reaction, learning, behaviour and results. We performed a continuous course evaluation, assessed the respective learning goal attainment, conducted a pre-post evaluation of reasons and goals for participation in the training, and measured the treatment effects on the patient side. Results: The implementation of training standards in the field of psychosomatic medicine and psychotherapy for medical doctors and the transfer of didactic knowledge and skills for Chinese lecturers were achieved. A total of 142 mainly medical doctors attended the 2-year training. Ten medical doctors were trained as future teachers. All learning goals were reached. The content and didactics of the curriculum were rated with an overall grade of 1.23 (1= very good to 5= very bad). The highest rated elements were patient life interviews, orientation on clinical practice and communication skills training. The achievement of learning objectives for each block (depression, anxiety disorders, somatic symptom disorder, coping with physical diseases) was rated between 1 and 2 (1 = very well achieved to 5 = not achieved) for all items from participants' perspectives. On the patient side (n=415), emotional distress decreased and quality of life and the doctor–patient alliance improved significantly. Discussion: Advanced training in psychosomatic medicine and psychotherapy was successfully implemented. The results of the evaluation show high participant satisfaction and the successful achievement of all learning objectives. A more detailed and extensive evaluation of the data, such as an analysis of the development of the participants as psychotherapists, is in preparation. The continuation of the training under Chinese guidance is guaranteed.